Pengaruh Perceived Quality, Customer Engagement, Perceived Value Dan Satisfaction Terhadap Future Intention Pada Pusat Kebugaran - Santi, Lidia Chris; Diatmika, Anak Agung Ketut; Sofyan, Joel Faruk (Jurnal sosial dan sains, 2025)
This study aims to analyze the influence of Perceived Quality, Customer Engagement, Perceived Value, and Satisfaction on Future Intention of fitness center service users. This study is motivated by the importance of maintaining Future Intention through their Perceived Quality, Customer Engagement, Perceived Value, and Satisfaction towards the services provided. The research method used is quantitative with data collection techniques using questionnaires distributed to fitness center users and analyzed using the Structural Equation Modeling (SEM) method. The results of the study show that of the six hypotheses proposed, three of them are proven significant, namely the influence of Customer Engagement on Perceived Value, Perceived Value on Satisfaction, and Satisfaction on Future Intention. Meanwhile, the other three hypotheses, namely the influence of Perceived Quality on Perceived Value, Perceived Quality on Satisfaction, and Customer Engagement on Satisfaction, do not show a significant influence. These findings indicate that Customer Engagement plays a significant role in increasing Perceived Value, which in turn positively impacts Satisfaction and Future Intention to continue using fitness center services. Perceived Service Quality does not necessarily directly shape Perceived Value or satisfaction, so a more comprehensive strategy is needed to improve overall Future Intention.